Resveratrol: A Sirtuin Activator and The Fountain of Youth - Meiliana, Anna; Dewi, Nurrani Mustika; Wijaya, Andi (The Prodia Education and Research Institute (PERI), 2015)
BACKGROUND: An organism’s lifespan is inevitably accompanied by the aging process, which involves functional decline, a steady increase of a plethora of chronic diseases, and ultimately death. Thus, it has been an ongoing dream of mankind to improve healthspan and extend life.CONTENT: There are only a few proposed aging interventions: caloric restriction, exercise, and the use of low-molecular-weight compounds, including spermidine, metformin, resveratrol, and rapamycin. Resveratrol, a constituent of red wine, has long been suspected to have cardioprotective effects. Interest in this compound has been renewed in recent years, first from its identification as a chemopreventive agent for skin cancer, and subsequently from reports that it activates sirtuin deacetylases and extends the lifespans of lower organisms. Resveratrol have been shown to prevent and reduce the severity of age-related diseases such as atherosclerosis, stroke, myocardial infarct, diabetes, neurodegenerative diseases, osteoarthritis, tumors and metabolic syndrome, along with their ability to extend lifespan.SUMMARY: The purpose of aging research is the identification of interventions that may avoid or ameliorate the ravages of time. In other words, the quest is for healthy aging, where improved longevity is coupled to a corresponding healthspan extension. It is only by extending the healthy human lifespan that we will truly meet the premise of the Roman poet Cicero: “No one is so old as to think that he may not live a year.”KEYWORDS: aging, caloric restriction, mimetic, healthspan, sirtuin activator